2020
DOI: 10.3389/fneur.2020.567891
|View full text |Cite
|
Sign up to set email alerts
|

PasoDoble, a Proposed Dance/Music for People With Parkinson's Disease and Their Caregivers

Abstract: Managing the heterogeneity of Parkinson's disease symptoms and its progressive nature demands strategies targeting the hallmark disrupted neurotransmission but also the comorbid derangements and bolstering neuroprotection and regeneration. Strong efforts are done to find disease-modifying strategies, since slowing disease progression is not enough to hamper its burden and some motor symptoms are resistant to dopamine-replacement therapy. The inclusion of non-pharmacological strategies can provide such a multit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Falls result from complex interactions between internal and external factors (Franco et al, 2020 ). Among internal factors, balance and mobility are core risk factors and preventive factors that can be altered (Giménez-Llort and Castillo-Mariqueo, 2020 ). Considering that the balance function of people with cognitive impairment is worse than that of healthy older adults, older people with MCI tend to have higher fall rates (Fuentes-Abolafio et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Falls result from complex interactions between internal and external factors (Franco et al, 2020 ). Among internal factors, balance and mobility are core risk factors and preventive factors that can be altered (Giménez-Llort and Castillo-Mariqueo, 2020 ). Considering that the balance function of people with cognitive impairment is worse than that of healthy older adults, older people with MCI tend to have higher fall rates (Fuentes-Abolafio et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dance enhances social connection, reduces stress and tension, and boosts confidence and self-esteem leading to an overall improvement in mood [ 7 , 12 ]. In addition, research on dance in PD has shown improvements in patient-caregiver QoL [ 13 ] thus we encouraged the caregivers to enroll in the class.…”
Section: Introductionmentioning
confidence: 99%